Detection of elastin, collagen, and cartilage particles in ground beef by enzyme digestion and sensory analysis - G. Whipple; J.B. Axe; S. Goll; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 1987)
An enzyme digestion technique was developed using a proteolytic enzyme concentrate to quantitate connective tissue particles in ground beef samples, which had been formulated to contain various amounts of connective tissue. Replicate samples were also evaluated by a taste panel to quantify detectable connective tissue particles. Results for the laboratory enzyme technique and the taste panel were highly correlated. Therefore, the enzyme digestion technique can be used to estimate total connective tissue in ground beef and those particles that are detected upon chewing.
Keywords: Cattlemen' s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Elastin; Collagen; Cartilage; Ground Beef